Evaluating the Impact of Flexibilities from Heating and Electromobility in Chile’s Carbon Neutrality Pathway - Abhishake Kundu; Francisco Flores; Carlos A. A. Fernández Vázquez; Humberto Godoy; Sylvain Quoilin; Monica Castaneda; Felipe Feijoo (Buildings)
Chile’s commitment to achieve carbon neutrality by 2050 underscores the need for robust decarbonization strategies across various sectors. Despite making progress in integrating renewable energy, sectors like transportation and residential heating, which are heavily reliant on fossil fuels, present significant opportunities for decarbonization. This study develops and evaluates pathways based on Chile’s Long-Term Energy Plan for assessing the effect of flexibilities from the power-to-heat and power-to-transportation sectors. Using EnergyPLAN, we model different scenarios of Chile’s 2050 energy plan that incorporate varying levels of individual heating and electromobility and assess their impacts on excess (surplus) electricity generation, different cost metrics, and renewable energy penetration. Findings indicate that increasing flexibility within the transportation sector through smart charging and vehicle-to-grid technologies can reduce excess generation, enhance grid stability, and lower operational costs. Flexibilities in individual heating, when coupled with more renewable energy capacity, show the potential to decrease reliance on fossil fuels significantly. The evidence of major efficiency gains in Chile’s 2050 energy plan, which is achievable by investing in heating and transportation flexibilities and further augmented by the country’s unique renewable potential, should interest stakeholders. Future work will focus on optimizing these technologies to address Chile’s specific infrastructure and regulatory challenges.